Spontaneous metathesis of bis-chelated PdII(L-S,O)2 complexes in solution : a rp-HPLC study - Van der Molen, Lynndal (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Chemistry and Polymer Science))--Stellenbosch University, 2008.